2016
DOI: 10.1161/strokeaha.115.009955
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Implications of Intracranial Arterial Remodeling in Stroke Patients

Abstract: Background and Purpose Preliminary studies suggest ntracranial arteries are capable of accommodating plaque formation by remodeling. We sought to study the ability and extent of intracranial arteries to remodel using 3D high-resolution black blood MRI (BBMRI) and investigate its relation to ischemic events. Methods 42 patients with cerebrovascular ischemic events underwent 3D time-of-flight MRA and contrast-enhanced BBMRI examinations at 3T for intracranial atherosclerotic disease. Each plaque was classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 36 publications
10
139
2
1
Order By: Relevance
“…Second, the study recruited patients with strokes in the anterior circulation only. Therefore, our conclusion has to be extrapolated to the posterior circulation with caution, given the reported evidence about the morphological difference in plaques between the 2 vascular sites 8. Last, the features explored in this study are still limited.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, the study recruited patients with strokes in the anterior circulation only. Therefore, our conclusion has to be extrapolated to the posterior circulation with caution, given the reported evidence about the morphological difference in plaques between the 2 vascular sites 8. Last, the features explored in this study are still limited.…”
Section: Discussionmentioning
confidence: 85%
“…The solution currently available to clinicians heavily relies on luminography imaging, with which the stenotic degree is a primary criterion for defining a culprit or high‐risk lesion. However, extensive research on the atherosclerosis disease has suggested that lumen narrowing may not be a reliable indicator of plaque severity because of positive remodeling of the vessel wall,8 and the features exhibited directly by plaques may provide complementary information 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…For optimal CNR, not only suppression of blood signal to depict the inner boundary of the VW, but also suppression of CSF signal to depict the outer boundary is essential, especially when outward vascular remodeling is present (27)(28)(29)(30). At 3 T, the CNR between VW and lumen is superior to the CNR between VW and CSF on most pulse sequences.…”
Section: How I Do It: the Use And Pitfalls Of Intracranial Vessel Walmentioning
confidence: 99%
“…Posterior circulation plaques may be particularly underestimated by angiographic means because the basilar artery exhibits a propensity towards positive remodelling and the posterior circulation is predisposed to perforator occlusion [1416]. Vertebrobasilar artery stenosis confers a significant risk of stroke, myocardial infarction and death [17].…”
Section: Introductionmentioning
confidence: 99%